Lingual and Maxillary Labial Frenuloplasty with Myofunctional Therapy as a Treatment for Mouth Breathing and Snoring - Chirag Govardhan; Janine Murdock; Leyli Norouz-Knutsen; Sanda Valcu-Pinkerton; Soroush Zaghi (Case Reports in Otolaryngology)
Chronic mouth breathing may adversely affect craniofacial development in children and may result in anatomical changes that directly impact the stability and collapsibility of the upper airway during sleep. Mouth breathing is a multifactorial problem that can be attributed to structural, functional, and neurological etiologies, which are not all mutually exclusive. While therapeutic interventions (myofunctional, speech and swallowing, occupational, and craniosacral therapy) may address the functional and behavioral factors that contribute to mouth breathing, progress may sometimes be limited by restrictive lingual and labial frenum that interfere with tongue and lip mobility. This case report explores the case of a three-year-old girl with mouth breathing, snoring, noisy breathing, and oral phase dysphagia that was successfully treated with lingual and labial frenuloplasty as an adjunct to myofunctional therapy. Within four days of the procedure, the patient had stopped snoring and demonstrated complete resolution of open mouth breathing. The patient was also observed to have increased compliance with myofunctional therapy exercises. This report highlights the effectiveness of surgical interventions to improve the efficacy of myofunctional therapy in addressing open mouth posture and low tongue resting position.